2021
DOI: 10.1038/s41598-021-88307-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of blood biomarkers and autoimmunity with immune related adverse events in patients with cancer treated with immune checkpoint inhibitors

Abstract: Patients with cancer treated with immune checkpoint inhibitors (ICIs) develop immune related adverse events (irAEs), however biomarkers are lacking. We hypothesized that clinicopathologic and laboratory factors would be associated with irAE risk and overall survival (OS) in this population. In a retrospective study of patients treated with ICIs we collected clinicopathologic, laboratory, irAEs and outcomes data. The association between baseline blood biomarkers, clinicopathologic features and irAEs was assesse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 40 publications
0
44
0
Order By: Relevance
“…[15][16][17][18] In a recent study of patients with various cancers receiving ICI treatment, a low level of NLR (< 5.3) was significantly associated with development of irAEs and longer OS. 15 In NSCLC patients treated with anti-PD-(L)1 antibodies, NLR <3 was significantly correlated with irAEs. 16 In addition, a different cohort study revealed that pretreatment with NLR ≥ 5 was associated with worse OS outcomes in patients with NSCLC treated with nivolumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18] In a recent study of patients with various cancers receiving ICI treatment, a low level of NLR (< 5.3) was significantly associated with development of irAEs and longer OS. 15 In NSCLC patients treated with anti-PD-(L)1 antibodies, NLR <3 was significantly correlated with irAEs. 16 In addition, a different cohort study revealed that pretreatment with NLR ≥ 5 was associated with worse OS outcomes in patients with NSCLC treated with nivolumab.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between NLR, irAE development and outcomes has been reported in several studies. [15][16][17][18] In a recent study of patients with various cancers receiving ICI treatment, a low level of NLR (< 5.3) was significantly associated with development of irAEs and longer OS. 15 In NSCLC patients treated with anti-PD-(L)1 antibodies, NLR <3 was significantly correlated with irAEs.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-existing autoimmune disease (AD) and even a family history of it seems to increase the risk of irAE in patients treated with ICI ( 41 43 ). Contrary to most studies, a small study with 56 NSCLCs treated with PD-1 inhibitors, the incidence of irAE was not that different from the trials that excluded patients with AD ( 76 ).…”
Section: Patient-specific Risk Factors For Iraementioning
confidence: 99%
“…With respect to irAE, we found a significant cut-off of 0.51 for monocytes, where higher monocyte counts corresponded to an increased odds of developing an irAE. Increased baseline monocyte counts were already associated with the development of irAE in other studies, but also with weak p -values [ 36 ]. We also found monocytes to be significant with respect to the survival random forest for irAE ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 96%